Predicting histologic grades for pancreatic neuroendocrine tumors by radiologic image-based artificial intelligence: a systematic review and meta-analysis - Yan, Qian; Chen, Yubin; Liu, Chunsheng; Shi, Hexian; Han, Mingqian; Wu, Zelong; Huang, Shanzhou; Zhang, Chuanzhao; Hou, Baohua (Frontiers in Oncology, 2024)
Background: Accurate detection of the histological grade of pancreatic neuroendocrine tumors (PNETs) is important for patients' prognoses and treatment. Here, we investigated the performance of radiological image-based artificial intelligence (AI) models in predicting histological grades using meta-analysis.Method: A systematic literature search was performed for studies published before September 2023. Study characteristics and diagnostic measures were extracted. Estimates were pooled using random-effects meta-analysis. Evaluation of risk of bias was performed by the QUADAS-2 tool.Results: A total of 26 studies were included, 20 of which met the meta-analysis criteria. We found that the AI-based models had high area under the curve (AUC) values and showed moderate predictive value. The pooled distinguishing abilities between different grades of PNETs were 0.89 [0.84 -0.90]. By performing subgroup analysis, we found that the radiomics feature-only models had a predictive value of 0.90 [0.87 -0.92] with I 2 =89.91%, while the pooled AUC value of the combined group was 0.81 [0.77 -0.84] with I 2 =41.54%.The validation group had a pooled AUC of 0.84 [0.81 -0.87] without heterogenicity, whereas the validation-free group had high heterogenicity (I 2 =91.65%, P=0.000). The machine learning group had a pooled AUC of 0.83 [0.80 -0.86] with I 2 =82.28%.: AI can be considered as a potential tool to detect histological PNETs grades. Sample diversity, lack of external validation, imaging modalities, inconsistent radiomics feature extraction across platforms, different modeling algorithms and software choices were sources of heterogeneity. Standardized imaging, transparent statistical methodologies for feature selection and model development ars still needed in the future to achieve the 5 transformation of radiomics results into clinical applications.